(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The study was aimed at determining the effects of Vitamin C and electrolyte on growth and meat yield of broilers in a hot humid environment. A total of 60 straight run day old Cobb 500 broilers were reared up to 35 days of age and fed ad libitum on a starter diet up to 12 days and thereafter, on a grower diet. The broilers were divided into 4 treatment groups. One group (15 broilers) without Vitamin C and electrolyte supplementation was considered as control. In other three groups were provided 135ppm Vitamin C, 1250ppm electrolyte and 135ppm Vitamin C + 1250ppm electrolyte in drinking water respectively as supplement. Feed intake, body weight, feed conversion and survivability were similar in broilers that received different levels of Vitamin C and electrolyte supplementation in drinking water. Feed cost per broiler and per kg broiler increased due to the addition of Vitamin C and electrolyte. Dressing yield, breast meat, total meat and wing meat were (P<0.05) higher in broilers that received Vitamin C in drinking water than those of control, electrolyte and Vitamin C + electrolyte supplemented groups. No differences (P>0.05) were found in breast: dark meat, thigh meat, drumstick meat and abdominal fat which could be attributed to either Vitamin C or electrolyte supplementation. It implies that deficiency of Vitamin C may be related to reduce meat yield of broilers in a hot humid environment. However, further experiment using several doses of Vitamin C with large number of broilers may be conducted to confirm the appropriate doses of supplementation. Keywords: Vitamin C; Electrolyte; Broiler growth; Meat yield DOI: 10.3329/jbau.v8i1.6399 J. Bangladesh Agril. Univ. 8(1): 57-60, 2010